Induction of Apoptosis in U937 Cells by Using a Combination of Bortezomib and Low-Intensity Ultrasound - Saliev, Timur; Feril Jr., Loreto B.; Ogawa, Koichi; Watanabe, Akiko; Begimbetova, Dinara; Molkenov, Askhat; Alimbetov, Dauren; Tachibana, Katsuro (Medical Science Monitor, 2016)
Background: We scrutinized the feasibility of apoptosis induction in blood cancer cells by means of low-intensity ultrasoundand the proteasome inhibitor bortezomib (Velcade). Material/Methods: Human leukemic monocyte lymphoma U937 cells were subjected to ultrasound in the presence of bortezomib and the echo contrast agent Sonazoid. Two types of acoustic intensity (0.18 W/cm2 and 0.05 W/cm2) were used for the experiments. Treated U937 cells were analyzed for viability and levels of early and late apoptosis. In addition, scanning electron microscopy analysis of treated cells was performed. Results: The percentage of cells that underwent early apoptosis in the group treated with ultrasound and Sonazoid was 8.0±1.31% (intensity 0.18 W/cm2) and 7.0±1.69% (0.05 W/cm2). However, coupling of bortezomib and Sonazoid resulted in an increase in the percentage of cells in the early apoptosis phase, up to 32.50±3.59% (intensity 0.18 W/cm2) and 33.0±4.90% (0.05 W/cm2). The percentage of U937 cells in the late apoptosis stage was not significantly different from that in the group treated with bortezomib only. Conclusions: Our findings indicate the feasibility of apoptosis induction in blood cancer cells by using a combination of bortezomib, ultrasound contrast agents, and low-intensity ultrasound.
Keywords: antineoplastic protocols; apoptosis; lymphoma; sound; Research Subject Categories::MEDICINE